Stakeholder Functions in Policy Implementation for Higher Education in Cameroon - Berka Tah Delphine Sakwe (An Overview of Literature, Language and Education Research Vol. 9, 2025)
This chapter explores the key elements of stakeholder engagement in the implementation of educational policies within higher education institutions in Cameroon. Drawing on existing literature and empirical evidence, the chapter highlights key elements that are essential for effective stakeholder engagement in the policy implementation process. Policies are living documents that require various inputs to assist in fulfilling their goals, and as such attention to policy issues does not end at the creation of the policy. Its implementation is increasingly a multi-sectored endeavour and a successful policy process requires democratic public participation, wherein in the national sphere, different stakeholders get involved to reduce the political pressure on the government and thus achieve its objectives. Yet, this engagement might not continue during the policy implementation stage. The chapter is an exploratory study, that makes use of the qualitative approach and phenomenology method. Qualitative data was analyzed using thematic analysis. Using the purposive sampling technique, 50 stakeholders including government officials, academic staff, students, employers and community members were interviewed to examine their roles and perspectives. Findings indicate that all-inclusive stakeholder engagement in educational policies can lead to more inclusive, effective and sustainable policies that benefit all members of the community. As such recommendations for enhancing stakeholder collaboration and participation in policy implementation are also discussed, with a focus on promoting transparency, inclusivity, and accountability in decision-making processes. The chapter also concludes with the proposition that implementation failure is partly due to a lack of stakeholder engagement.